2006
DOI: 10.1002/jhet.5570430643
|View full text |Cite
|
Sign up to set email alerts
|

First synthesis of furo[3,4‐c]coumarins

Abstract: Various 1,3‐dimethyl and 1‐methyl‐3‐phenylfuro[3,4‐c]coumarins (5a‐h and 6a‐h) have been synthesized by demethylation cyclization of the respective 3‐aryl‐4‐ethoxycarbonyl furans (3a‐h and 4a‐h). These ethoxycarbonyl furans were prepared by reacting appropriate 1‐aryl‐2‐nitro‐prop‐1‐ene (1a‐h) with ethyl acetoacetate or ethyl benzoylacetate under Nef reaction condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…(Scheme 1, 4m-p). As expected, due to the steric hindrance coming from R 4 , the products contained two regioisomers 5 and 6 when R 4 became bulkier so that the addition of Bu 3 P towards 4 took place less selectively (Scheme 1, 4m vs. 4n-p). It could be assumed that the R 4 substituent served as a blocking group for b¢-addition, but a small R 4 had little effect on the regiocontrol of the Michael addition of Bu 3 P (Scheme 1, 4n-p vs. Table 4 entries 1-12).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…(Scheme 1, 4m-p). As expected, due to the steric hindrance coming from R 4 , the products contained two regioisomers 5 and 6 when R 4 became bulkier so that the addition of Bu 3 P towards 4 took place less selectively (Scheme 1, 4m vs. 4n-p). It could be assumed that the R 4 substituent served as a blocking group for b¢-addition, but a small R 4 had little effect on the regiocontrol of the Michael addition of Bu 3 P (Scheme 1, 4n-p vs. Table 4 entries 1-12).…”
Section: Resultssupporting
confidence: 64%
“…Furthermore, among the three possible structural isomers with furan fused on the lactone ring, only one report to the best of our knowledge is published for the syntheses of furo [3,4-c]coumarins. 4 In 2006, Brahmbhatt 4 and co-workers demonstrated that furo [3,4-c]coumarins could be synthesized by the demethylation-cyclization of 3-aryl-4-ethoxycarbonyl furans, which were prepared from b-methyl-b-nitrostyrenes through Nef reactions. However, their application has been limited due to difficulties in tolerating a broad range of functional groups, which is a result of high temperatures and harsh reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Ad ifferent approach to regioisomericf urocoumarins 266 employs nitrostyrenes 264 which uponr eaction with b-keto esters in the presenceo fp iperidine affordf ullys ubstituted furans 265 (Scheme85). [165] Theo verall transformation involves ap reliminary conjugate addition followed by the Nefr eactiona nd finally as pontaneous Paal-Knorr ring closure.C onversion of furans 265 into the corresponding furocoumarins 266 is realized using HBr in boiling acetic acid.…”
Section: Five-memberedring Systemsmentioning
confidence: 99%
“…In addition, the preparation of 3-aryl-4ethoxycarbonyl furans 71 from substituted benzaldehydes via bmethyl-b-nitrostyrenes is laborious and low-yielding. 66 Enones can serve as strong acceptors of phosphines and can be smoothly converted into furans via phosphorus ylides as intermediates. 67 On this basis, a new synthesis of highly functionalized furo[3,4-c]coumarins 74 was developed, based on the treatment of coumarins 73 with acyl chlorides and n-tributylphosphine in the presence of triethylamine (Scheme 24).…”
Section: Synthesis Of Coumarin-linked and Coumarin-fused Heterocyclesmentioning
confidence: 99%